THE EFFECT OF DEMOCRATIC LEADERSHIP STYLE ON THE PERFORMANCE OF EMPLOYEES AT THE MALAWEI COMMUNITY HEALTH CENTER IN SORONG CITY - Ade Andriani Renouw; Andrei Maryen; Meylani Lusye Fransina Ayer (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study was to determine the effect of democratic leadership style on employee performance at the Malawei Community Health Center. The analysis technique used was descriptive quantitative analysis using SPSS 26 software. The results showed a significant value of less than 5% (0.05), indicating that democratic leadership style influences employee performance at the Malawei Community Health Center. Therefore, the hypothesis (Ho) is rejected and H1 is accepted. The R² test obtained an R² value of 0.245, indicating that the contribution of democratic leadership style to employee performance at the Malawei Community Health Center is 24.5%, with the remaining 75.5% influenced by variables outside the study.